Forests, Democracy and the Forest Service - Wood, P. J. (Indian Forester, 2001)
Forests and Forest services cater to the basic needs of the people and have to maintained and even expanded on a sustainable basis. Democracy has added new concepts of transparency besides scientific management. International requirements have also to be met related to biodiversity, environmental quality etc. In the new developments of democratic institutions, several new approaches ego privatisation, Joint Forest Management have been tried with varying success, although in some cases new problems have also cropped up. These new developments have been critically examined. The forest services are now required to maximise revenue, in some cases even self-financing, enhance environmental quality, develop recreational and educative potential and to facilitate access of the public to the forests. It has also to function efficiently, effectively and sympathetically. It is also required to strike a balance between the demands of various stakeholders and provide equality of rights and opportunity guaranteed in the constitutions. In conclusion it has been suggested that goods and services expected of forests should be re-examined and the public should appraise the policy decisions democratically. The interest of persons dependent on forests should be protected and catered for on priority as compared to other sectors and their demands. The essential requiremcnts of policy should be worked out and while delegating authority and/or management, it should be ensured that these are carried out satisfactorily and effectively. The interest of the nation will have to be safeguarded.